Kemampuan berpikir kritis mahasiswa perempuan pada level abstraksi Van Hiele - Aini, Septi Daryatul; Nuritasari, Fetty; Supardi, Lili; Nafiah, Siti (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2021)
Critical thinking abilities are very important to improve the quality of thinking and make students better understand the content that has been studied. But in reality, students' critical thinking skills are still very low. So it is necessary to have a study that describes the critical thinking skills of these students . The purpose of this study is to describe students' critical thinking skills at the abstraction level in solving space construction problems. This research is a qualitative descriptive type because it describes in detail the critical thinking ability of Van Hiele's abstraction level in solving space construction problems. The instruments of this research are the van Hiele geometry test, the space construction problem solving test, and the interview guide. The research subjects consisted of one student of class VIII of SMP Negeri 2 Pamekasan at the Van Hiele level of Abstraction. The selection of female subjects in this study was due to the fact that female subjects were more communicative in expressing what was in their minds making it easier for researchers to uncover critical thinking of students at the level of Van Hiele abstraction. The results showed that the subject solved the space construction problem according to the critical thinking indicator stage but was not perfect because the subject made an error when solving the problem (indicator evaluation), so that the final answer obtained was not correct. This affects the conclusions obtained (inference indicators) namely the subject draws conclusions but the answers are not correct.